Low serum 25‐hydroxyvitamin D concentrations associate with non‐alcoholic fatty liver disease in adolescents independent of adiposity. Issue 6 (June 2014) - Black, Lucinda J; Jacoby, Peter; She Ping‐Delfos, Wendy Chan; Mori, Trevor A; Beilin, Lawrence J; Olynyk, John K; Ayonrinde, Oyekoya T; Huang, Rae Chi; Holt, Patrick G; Hart, Prue H; Oddy, Wendy H; Adams, Leon A
Abstract Background and Aims Non‐alcoholic fatty liver disease (NAFLD) and serum 25‐hydroxyvitamin D (s25[OH]D) concentrations are both associated with adiposity and insulin resistance (IR) and thus may be pathogenically linked. We aimed to determine the prevalence of vitamin D deficiency in adolescents with NAFLD and to investigate the prospective and cross‐sectional associations between s25[OH]D concentrations and NAFLD. Methods Participants in the population‐based West Australian Pregnancy (Raine) Cohort had seasonally adjusted s25(OH)D concentrations determined at ages 14 and then 17 years. NAFLD was diagnosed at 17 years using liver ultrasonography. Associations were examined after adjusting for potential confounders. Odds ratios (ORs) and confidence intervals (CIs) are reported per standard deviation in s25(OH)D concentrations. Results NAFLD was present in 16% (156/994) of adolescents. The majority of participants with NAFLD had either insufficient (51%) or deficient (17%) vitamin D status. s25(OH)D concentrations at 17 years were inversely associated with risk of NAFLD (OR 0.74, 95% CI 0.56, 0.97; P = 0.029), after adjusting for sex, race, physical activity, television/computer viewing, body mass index, and IR. The effect of s25(OH)D concentrations at 17 years was minimally affected after further adjusting for s25(OH)D concentrations at 14 years (OR 0.76, 95% CI 0.56, 1.03; P = 0.072). Conclusions Lower s25(OH)D concentrations are significantly associated with NAFLD, independent of adiposity and IR. Screening for vitamin D deficiency in adolescents at risk of NAFLD is appropriate, and clinical trials investigating the effect of vitamin D supplementation in the prevention and treatment of NAFLD may be warranted.